Design of High-Speed Motor System for EV Based on 1200 V SiC-MOSFET Power Module - Kun Zhou; Minglei Gu; Yu Zheng (Actuators)
In this paper, a high-speed motor system for an Electric Vehicle (EV) is designed, of which the rated DC-link voltage is 800 V and peak power can reach 200 kW with a high-efficiency Silicon Carbide Metal Oxide Semiconductor Field Effect Transistor (SiC-MOSFET). With the help of optimization motor design methods, such as pole–slot combination optimization, process optimization and control optimization, the motor can reach its maximal speed of 25,000 rpm and maximal torque of 240 Nm. Finally, the performance of the high-voltage motor system based on the SiC-MOSFET power module is evaluated by simulation and experiment.